Halal Lifestyle Understanding Among Students in the Digital Era - Komaria, Yulisa Nurul; Maadi, Alan Su’ud (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic boarding schools in Indonesia play a central role in transmitting Islamic values and shaping ethical student behavior. Specific Background: In the digital era, their relevance is increasingly tested, particularly in guiding students to understand and practice a halal lifestyle across food, beverages, clothing, and digital activities. Knowledge Gap: Despite their strategic role, many pesantren still face limited halal literacy and have not fully integrated halal principles into students’ daily practices. Aims: This study analyzes the role of the Syaichona Moh Cholil Islamic Boarding School in improving students’ understanding and application of halal lifestyle values in a digitalized environment. Results: The findings show that the pesantren enforces strict supervision of halal food and beverages, applies sharia-based dress codes, and builds halal-oriented habits through structured education and daily routines. Digital innovations such as student digital cards, technology-supported learning, and the use of social media further strengthen halal-based economic and behavioral systems. Novelty: This research presents the integration of classical Islamic education with digital transformation to reinforce halal lifestyle awareness. Implications: These findings affirm the potential of pesantren as adaptive institutions capable of enhancing halal literacy and forming digitally competent, ethically grounded future generations. Highlights: Strengthens students’ halal literacy through daily supervision and education. Integrates digital tools to support halal-based financial and learning systems. Combines classical Islamic values with modern technological adaptation. Keywords: Halal Lifestyle, Islamic Boarding School, Digitalization, Students, Sharia Values